An econometric study of the effects of airport privatization on airfares in Brazil. (December 2021) - Brito, Igor R.S.; Oliveira, Alessandro V.M.; Dresner, Martin E.
Abstract: This paper develops empirical models to test the impact of airport privatization on airline fares. We employ a difference-in-difference approach combined with an endogenous switching regression model to account for the selection of airports to be privatized. The results suggest that prices for tickets on routes with at least one privatized airport at an endpoint are about 3–3.5% higher than on routes between two publicly managed airports. By testing moderating effects, we find evidence that market dominance enforces the privatization impact on airfares. The main conclusions are consistent using various control group classifications. Highlights: We estimate an econometric model of airline pricing. We test the hypothesis of higher airfares due to airport privatization. We employ difference-in-difference approach combined with a two-stage switching regression. We select instrumental variables and regressors using fixed effects, post-double IV-LASSO. Results corroborate the raised hypothesis.